2017
DOI: 10.3354/ab00678
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutritional parameters in diploid and triploid African catfish Clarias gariepinus following chlorpyrifos exposure

Abstract: There is a paucity of information about the influence of ploidy status on physiological parameters in organisms following contaminant stress. Also, little is known about the changes in nutritional values of fishes in response to the exposure to contaminants. Full-sibling juvenile Clarias gariepinus were exposed to 3 levels (mean measured 8.9, 17.5, or 28.0 µg l −1 ) of chlorpyrifos for 21 d. The levels of 3 fatty acids (FAs) in the muscle were significantly different between unexposed diploid and triploid fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…Chronic exposure to hexavalent chromium significantly altered the proximate composition of the animals, especially the protein content, which reduced significantly in all the tissues of the exposed animals, especially at the highest exposure concentration. The decreased protein content in the exposed animals has been reported in other studies [45,46]. The protein content of the fish African catfish decreased significantly following exposure to chlorpyrifos [45].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Chronic exposure to hexavalent chromium significantly altered the proximate composition of the animals, especially the protein content, which reduced significantly in all the tissues of the exposed animals, especially at the highest exposure concentration. The decreased protein content in the exposed animals has been reported in other studies [45,46]. The protein content of the fish African catfish decreased significantly following exposure to chlorpyrifos [45].…”
Section: Discussionsupporting
confidence: 78%
“…The decreased protein content in the exposed animals has been reported in other studies [45,46]. The protein content of the fish African catfish decreased significantly following exposure to chlorpyrifos [45]. Also, Sohail et al [46] reported a significant decrease in the protein contents in the tissues of the freshwater mussel, Anodonta anatina.…”
Section: Discussionsupporting
confidence: 52%
“…[27] observed a decrease in protein in L. rohita after exposure to chlorpyrifos. [28] reported that unexposed fish might exhibit better nutritional composition compared to the fish treated with chlorpyrifos, which might be due to their better health and balance protein and lipid profile in the muscle of Clarias gariepinus. [29] reported a decrease in protein and fat content against sublethal exposure of 'Phorate 10G' in tilapia.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, contamination of fish destined for human consumption poses potential human health impacts [27,29]. Changes in nutritional parameters including skin gelatin, muscle protein content, amino acids and fatty acid compositions were reported in fish exposed to OPs [30][31].…”
Section: Introductionmentioning
confidence: 99%